GREB1L overexpression is associated with good clinical outcomes in breast cancer - Ke Dong; Chenchen Geng; Xiaohong Zhan; Zhi Sun; Qian Pu; Peng Li; Haiyun Song; Guanghui Zhao; Haidong Gao (European Journal of Medical Research, 2023)
Abstract Background Breast cancer is the most common malignant tumor among women worldwide. GREB1L is a protein-coding gene. Previous studies have shown that GREB1L plays a vital role in lung and gastric adenocarcinoma. Currently, there is no relevant report about its role in breast cancer. Methods The Cancer Genome Atlas database was used to compare the expression level of GREB1L between tumor and normal tissues. The TISIDB website was used for prognosis analysis. The LinkedOmics database was used to predict the potential biological mechanism of GREB1L in breast cancer. Immunohistochemistry was used to detect the GREB1L expression level in breast tissue. Western blotting was used to detect the GREB1L expression level in cell lines. Transwell assays, CCK-8 cell proliferation assays, and colony formation assays were used to detect the migration, invasion, proliferation, and colony formation abilities of cells. Subcutaneous xenograft models were used to detect the in vivo tumor formation abilities of cells. Results GREB1L is highly expressed in breast cancer tissues and breast cancer cells. KEGG enrichment analysis suggested that GREB1L participates in the regulation of the Hedgehog signaling pathway; changes in GREB1L expression affected the migration and invasion abilities of MCF7 and MDA-MB-231 cells. Although changes in GREB1L expression did not affect their proliferation and colony formation abilities in vitro and in vivo, they affected the expression of tumor metastasis-related genes in vivo. The overexpression of GREB1L in breast cancer predicted a favorable prognosis. Conclusion These results showed that GREB1L is involved in the development of breast cancer, and it may be a potential molecular marker for predicting the prognosis of breast cancer.